New lineage of scuticociliates dominates the ciliate community and bacterivory in hypolimnetic waters of a freshwater reservoir - Šimek, Karel; Asghar, Usman; Sonntag, Bettina; Kasalický, Vojtěch; Shabarova, Tanja; Mukherjee, Indranil (The ISME journal, 2025)
Deep, cold, and dark hypolimnia represent the largest volume of water in freshwater lakes with limited occurrences of phototrophs. However, the presence of prokaryotes supports populations of bacterivorous ciliates and heterotrophic nanoflagellates (HNF). Nevertheless, protistan bacterivory rates and the major hypolimnetic ciliate bacterivores are poorly documented. We conducted a high frequency sampling (three-times a week) in the oxic hypolimnion of a stratified mesoeutrophic reservoir during summer, characterized by stable physicochemical conditions and low water temperature. Using fluorescently labeled bacteria we estimated that ciliates and HNF contributed, on average, 30% and 70% to aggregated protistan bacterivory, respectively, and collectively removed about two thirds of daily hypolimnetic prokaryotic production. The ciliate community was analyzed by the quantitative protargol staining method. One scuticociliate morphotype dominated the hypolimnetic ciliate community, accounting for 82% of total ciliates and over 98% of total ciliate bacterivory, with average cell-specific uptake rate of 202 prokaryotes per hour. Moreover, long-amplicon sequencing revealed that the scuticociliate belongs to an unidentified clade closely related to the Ctedoctematidae and Eurystomatellidae families. The high-resolution sampling, microscopic, and sequencing methods allowed uncovering indigenous microbial food webs in the hypolimnetic environment and revealed a functional simplification of ciliate communities, dominated by a new bacterivorous scuticociliate lineage.
Keywords: Sequence Analysis, DNA; bacterivorous protists; sekvenční analýza DNA; cold hypolimnetic layer; new lineage of scuticociliates; Lakes; Phylogeny; Ciliophora; freshwater reservoir; fylogeneze; jezera; protistan bacterivory rates; sladká voda; Bacteria; Fresh Water; Oligohymenophorea